ANALYSIS OF THE EXTREME RAINFALL FREQUENCY IN BANGKA BELITUNG ISLANDS BASED ON CLIMATE HAZARDS GROUP INFRA-RED PRECIPITATION WITH STATIONS (CHIRPS) DATA - Fadholi, Akhmad (Jurnal Pendidikan Geografi Gea, 2018)
This study aimed to know the distribution of extreme rainfall frequency in Babel using CHIRPS data for 36 years from 1981-2016. The determination of extreme threshold value uses four methods, those are BMKG heavy rainfall threshold, Percentile-99, Quartile (Q3 + 3IQR) and Peak Over Threshold (POT). The results of frequency calculations on each grid are then mapped with Inverse Distance Weight (IDW) method in the ArcGIS application. However, there are five areas with different patterns of consistency. Northern Bangka especially in West Bangka regency is indicated as consistent high frequency area, consistent low frequency region is east coast of Bangka, while non-consistent area is west coast of Central Bangka to South Bangka regency. Two patterns in Belitung consistently show high frequency in the west and low in the east. The findings of these patterns are similar to the three zones of the season (ZOM) in Bangka established by BMKG. It can be a consideration to make ZOM in Belitung.